Study on LBW/SPF/DB technology of TA15 four-storey lightweight high strength cylinder. Issue 1 (1st December 2022) - He, X F; Ding, R; Liu, Z Q; Yang, X K; Zhao, Q Q; Zhang, Q
Abstract : This paper investigates the application of Laser beam prewelding/superplastic forming/diffusion bonding (LBW/SPF/DB) process in cylindrical parts. The forming die design and the processing process have been researched. A numerical simulation was carried out to determine the parameters of the superplastic forming/diffusion bonding process. The causes of defects are analysed and effective optimization methods are presented. In this paper, the main research contents are as follows, (1) Considering the characteristics of the structure and process of the workpiece, a design idea using a flapping tool and wedge fastening is presented. The process scheme for forming the core barrel step is described. (2) A laser welding power of 1300W and a welding rate of 1000mm/min were determined as the welding parameters for the SPF/DB process. The weld depth and weld width were considered suitable for parameters for laser welding. (3) The results of high temperature material performance indicate that 900 °C and a strain rate of 0.1s-1 strain rate were selected to simulate the forming process. (4) Verify the workpiece in accordance with the simulation parameters and evaluate defects, such as grooves on the surface of the workpiece and triangular areas between vertical bars. All the cylinders' indexes can meet the requirements, and the process quality is stable and controllable.